Pengaruh Pembelajaran Jarak Jauh Dengan Aplikasi Google Class Terhadap Hasil Belajar Mahasiswa - Niken Septantiningtyas (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2018)
This research is an application of research in accordance with the learning trend 4.0, namely the application of Online Applications as IT-Based Learning Media that has been developed by Google. Google class is an application of research developed with the theme of learning the Industrial Revolution 4.0, which is an application of an online-based application for students in conducting online lectures, this application can facilitate students on assignments given by lecturers to be done anywhere and anytime, this application also can make it easier for students to communicate online directly with lecturers who need a subject without having to exit the google class application, other than that in this application students can have discussions with friends in the same class to program the course. The google class application is used to facilitate communication between lecturers and students online and directly on the topic of the chapter being studied so that students better understand the aims and objectives desired by the lecturer. This study is a research that seeks a relationship between the application of distance learning using the Google class application with student learning outcomes, this is a quantitative study of research data tested with normality test, homogeneity test and hypothesis test. The research will be conducted in the even semester of the 2018-2019 school year in the sixth semester students at Nurul Jadid University.